Pin-Tract Infection in External Fixation of Long Bones in Mbujimayi, DR Congo. - Bamusua, Eugène Mukeba; Kabamba, Trésor Kabuya; Mutombo, Clément Kadima; Tshilunda, Joseph Ngandu; Musanzayi, Sébastien Mbuyi; Akinja, Séverin Uwonda (International Journal of Health Sciences, 2026)
Purpose: External fixation for long‑bone fractures is widely used in resource‑limited settings but carries a substantial risk of pin‑tract infection. This study aimed to describe the epidemiological, clinical, and bacteriological profile of pin‑tract infections in an under‑equipped environment. Methods: this longitudinal descriptive study was conducted from March 2023 to August 2025 in two healthcare facilities in Mbujimayi (DR Congo). Patients who underwent external fixation of a long bone were included, provided they received radioclinical follow-up, bacteriological examination of the pin tract, and post-removal evaluation. Data were analyzed using IBM SPSS 28.0. Results: Eighty-eight isolates out of 292 samples (30.1% of the pins) confirmed pin-tract infection, with at least one pin positive in 38 out of 52 patients (73.0%). Clinically, pin-tract infection presented with pain, edema, and drainage. Staphylococcus epidermidis (33%), Enterobacteriaceae (27.3%), and Staphylococcus aureus (22.7%) dominated the bacteriological profile. Therefore, external fixation is associated with a significant risk of pin-tract infection. The magnitude of this problem highlights the need for preventive strategies and targeted treatment based on local pathogen distribution. Unique Contribution to Theory, Practice and Policy: This study provides the first local bacteriological mapping of pin‑tract infections in Mbujimayi, quantifies their high prevalence in under‑resourced settings, and offers evidence‑based guidance for adapting prevention and antibiotic strategies to local microbial patterns.